The role of lung volume recruitment therapy in neuromuscular disease: a narrative review - Sheers, Nicole L.; O’Sullivan, Rachel; Howard, Mark E.; Berlowitz, David J. (Frontiers in Rehabilitation Sciences, 2023)
Respiratory muscle weakness results in substantial discomfort, disability and ultimately death in many neuromuscular diseases. Respiratory system impairment manifests as shallow breathing, poor cough and associated difficulty clearing mucus, respiratory tract infections, hypoventilation, sleep-disordered breathing and chronic ventilatory failure. Ventilatory support (i.e., non-invasive ventilation) is an established and key treatment for the latter. As survival outcomes improve for people living with many neuromuscular diseases, there is a shift towards more proactive and preventative chronic disease multi-disciplinary care models that aim to manage symptoms, improve morbidity and reduce mortality. Clinical care guidelines typically recommend therapies to improve cough effectiveness and mobilise mucus, with the aim of averting acute respiratory compromise or respiratory tract infections. Moreover, preventing recurrent infective episodes may prevent secondary parenchymal pathology and further lung function decline. Regular use of techniques that augment lung volume has similarly been recommended (volume recruitment). It has been speculated that enhancing lung inflation in people with respiratory muscle weakness when well, may improve respiratory system “flexibility”, mitigate restrictive chest wall disease, and slow lung volume decline. Unfortunately, clinical care guidelines are based largely on clinical rationale and consensus opinion rather than level A evidence. This narrative review outlines the physiological changes that occur in people with neuromuscular disease and how these changes impact on breathing, cough, and respiratory tract infections. The biological rationale for lung volume recruitment is provided and the clinical trials that examine the immediate, short-term and longer-term outcomes of lung volume recruitment in paediatric and adult neuromuscular diseases are presented and the results synthesized.